1994
DOI: 10.1126/science.266.5184.398
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Stratospheric O 3 by Radicals: In Situ Measurements of OH, HO 2 , NO, NO 2 , ClO, and BrO

Abstract: Simultaneous in situ measurements of the concentrations of OH, HO(2), ClO, BrO, NO, and NO(2) demonstrate the predominance of odd-hydrogen and halogen free-radical catalysis in determining the rate of removal of ozone in the lower stratosphere during May 1993. A single catalytic cycle, in which the rate-limiting step is the reaction of HO(2) with ozone, accounted for nearly one-half of the total O(3) removal in this region of the atmosphere. Halogen-radical chemistry was responsible for approximately one-third… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
201
1
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 392 publications
(206 citation statements)
references
References 26 publications
3
201
1
1
Order By: Relevance
“…The latter process is important because excessive exchange between the midlatitudes, where most pollutant is injected, and the tropics, where the pollutant would be lofted to higher altitudes, would lead to an unrealistically long stratospheric residence time. Strong transport into the tropics would allow nitrogen oxides from the exhaust to be transported to altitudes where they could destroy large amounts of ozone [Wennberg et al, 1994]. The realistic attenuation of the tropical seasonal cycle over the 370-to 450-K range suggests there is not excessive exchange with the midlatitudes just below the proposed cruise altitudes.…”
Section: Diagnosis Of Model Transport and Comparison With Observationmentioning
confidence: 99%
“…The latter process is important because excessive exchange between the midlatitudes, where most pollutant is injected, and the tropics, where the pollutant would be lofted to higher altitudes, would lead to an unrealistically long stratospheric residence time. Strong transport into the tropics would allow nitrogen oxides from the exhaust to be transported to altitudes where they could destroy large amounts of ozone [Wennberg et al, 1994]. The realistic attenuation of the tropical seasonal cycle over the 370-to 450-K range suggests there is not excessive exchange with the midlatitudes just below the proposed cruise altitudes.…”
Section: Diagnosis Of Model Transport and Comparison With Observationmentioning
confidence: 99%
“…30 cm downstream of the injector), determined by calibration to be 1.6 × 10 9 molecule cm −3 -was the same for all experiments. These HO 2 concentrations are ∼ 50 times higher than typical levels in the sunlit stratosphere (Wennberg et al, 1994). A reference fluorescence cell, in which a large concentration of OH was generated and detected by LIF, was used to facilitate the identification of OH lines and tune the laser wavelength.…”
Section: Ho 2 Generation and Detectionmentioning
confidence: 99%
“…In this investigation a borosilicate glass aerosol flow tube coupled with a sensitive HO 2 detector based on chemical conversion followed by laser-induced fluorescence detection of OH (George et al, 2013) has been used to study the kinetics of the heterogeneous reaction of HO 2 with airborne TiO 2 nanoparticles at different RH. While it has been possible here to study such kinetics over a range of RHs representative to those typically found in the lower stratosphere (< 40 %) (Wennberg et al, 1994), experimental limitations meant that experiments were only conducted at room temperature (∼ 293 K). The TOMCAT three-dimensional (3-D) chemical transport model (CTM;Chipperfield, 1999) has also been used to predict the likely impact of HO 2 uptake by TiO 2 particles on the stratospheric concentrations of HO 2 and O 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their photochemical reactions strongly influence the abundance of odd hydrogen radicals (HOx = OH + HO2) that dominate lower stratospheric ozone loss [Wennberg et al, 1994]. All three reservoir species originate in the troposphere and enter the lower stratosphere predominantly through the tropical tropopause by the Brewer-Dobson circulation [Brewer, 1949].…”
Section: Introductionmentioning
confidence: 99%